Experimental investigation of carbon-based nano-enhanced phase change materials assimilated photovoltaic thermal system: Energy, exergy and environmental assessment - Rajamony, Reji Kumar; Kumar Pandey, Adarsh Kumar; Nurhanis Sofiah, Abd Ghafar; Paw, Johnny Koh Siaw; Suraparaju, Subbarama Kousik; Fatehmulla, Amanullah; Chopra, Kapil; Samykano, Mahendran; Farade, Rizwan A. (Taiwan Institute of Chemical Engineers, 2025)
Photovoltaic thermal systems (PVT) are advanced systems designed to simultaneously generate heat and electricity. However, their commercial performance has not yet reached optimal levels, with efficient thermal regulation being a major challenge that directly affects energy production and efficiency. Methods: This research introduces an innovative approach to enhancing PVT system performance by integrating active water cooling with passive functionalized carbon-based nano-enhanced phase change materials (NePHACMs) as a cooling medium. Four configurations were studied: PV, PVT, PVT-PHACM, and PVT-NePHACM, with fluid flow rates of 0.4-0.8 L/min. Indoor experiments were conducted for PV and PVT systems, while TRNSYS simulations assessed PVT-PHACM and PVT-NePHACM systems. The exergy approach was used to evaluate the energy available for productive use and exergy loss and entropy generation have been analyzed to enhance the electrical energy and thermal storage of the system. Additionally, carbon mitigation and carbon credit gain for all configurations were discussed. Significant Findings: The NePHACM formulation significantly enhanced the system's thermal conductivity by 104%, reduced PV temperature, and improved both electrical and thermal energy production. The system achieved an overall energy efficiency of 85.02% and an exergy efficiency of 12.37%. Additionally, the hybrid system demonstrated exceptional effectiveness in reducing CO2 emissions, highlighting NePHACM's potential to improve PVT system commercialization, especially for nocturnal applications.